Towers of strength in turbulent times? Assessing the effectiveness of international support to peace and democracy in Kenya and Kyrgyzstan in the aftermath of interethnic violence - Charlotte Fiedler (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The main aim of this study is to assess and explain the influence (or lack thereof) of international engagement on significant political developments in countries struggling to consolidate peace and democracy. Therefore, the study analyses major milestones, or critical junctures, in Kenya's and Kyrgyzstan's peace and democratisation process. The two countries can both be considered fragile states – a group of countries with distinct challenges that the policy world is still struggling to effectively respond to. Similar critical junctures were analysed for the two countries, concentrating on international support for peace and democracy after both experienced major outbreaks of violence (2007 in Kenya; 2010 in Kyrgyzstan). More specifically, the focus lay on whether donors contributed to 1) ending and overcoming interethnic violence, 2) restructuring the political systems through new constitutions and 3) holding the first elections after violence had taken place. The analysis shows that first, donors had a considerably larger impact on the political process in Kenya than in Kyrgyzstan, second, that these two countries have been particularly struggling with state legitimacy and continue to do so and third, that three factors influenced international actors' success or failure to effectively promote peace and democracy in the two countries: cooperative vs. coercive forms of support, donor coordination and prioritising stability over democracy.
Keywords: 330; Governance; Sicherheit; Frieden und fragile Staaten